Signal‐Averaged ECG in the Diagnostic Workup for Arrhythmogenic Cardiomyopathy: Insights From the Nordic ARVC Registry - Aleksei A. Savelev; Eivind W. Aabel; Anneli Svensson; Pia Dahlberg; Alex Hørby Christensen; Trine Madsen; Henning Bundgaard; Tiina Heliö; Aevar Ulfarsson; Thor Edvardsen; Jesper H. Svendsen; Henrik K. Jensen; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The diagnostic role of signal‐averaged ECG (SAECG) in arrhythmogenic right ventricular cardiomyopathy (ARVC) has lately been questioned. We assessed the value of SAECG‐derived late ventricular potentials (LP) in ARVC diagnosis and its association with disease manifestations. Methods and Results Patients with definite ARVC diagnosis or genotype‐positive family members who underwent SAECG were included in register‐based observational study (n=357, mean age 41 years, 47% female, 43% probands). LP and terminal activation duration (TAD) were defined by Task Force Criteria 2010. We assessed the association of TAD and LP with structural RV abnormalities and ventricular tachycardia (VT), defined as sustained VT, appropriate implantable cardioverter‐defibrillator shock, aborted cardiac arrest, or sudden cardiac death, at diagnosis. LP were documented in 210 patients (59%) and abnormal TAD in 66 patients (18%). Each of the SAECG parameters was significantly associated with definite ARVC diagnosis in receiver‐operator characteristics curve analysis with area under the curve between 0.67 and 0.74. Exclusion of SAECG from diagnostic workup led to reclassification of 37 patients (16%) from definite to borderline ARVC (13 probands, 9 of whom had prevalent VT). Ninety patients (25%) had history of VT. LP, but not TAD, were associated with VT (adjusted odds ratio [ORadj], 2.42 [95%CI, 1.07–5.48]). LP had lower specificity (72% versus 97%) but higher sensitivity (71% versus 25%) for association with RV structural abnormalities than TAD. Conclusions In the Nordic ARVC cohort SAECG‐derived LP are associated with VT and structural RV abnormalities and were critical for ascertainment of ARVC diagnosis in 16% of patients with narrow QRS complexes, including 8% of all probands.